Pulmonary hypertension associated with neurofibromatosis type 1. (29th August 2018) - Jutant, Etienne-Marie; Girerd, Barbara; Jaïs, Xavier; Savale, Laurent; O'Connell, Caroline; Perros, Frederic; Sitbon, Olivier; Humbert, Marc; Montani, David
Neurofibromatosis type 1 (NF1), also known as von Recklinghausen disease, is a frequent autosomal dominant genetic disorder with a prevalence of 1 in 3000. Pulmonary hypertension (PH) associated with NF1 (PH-NF1) is a rare but severe complication of NF1 and is classified as Group 5 PH, defined as "PH with unclear and/or multifactorial mechanisms". A literature review in PubMed on the association between NF1 and PH identified 18 articles describing 31 cases. PH-NF1 was characterised by a female predominance, an advanced age at diagnosis, an association with parenchymal lung disease in two out of three cases and poor long-term prognosis. NF1 is generally associated with interstitial lung disease but some cases of severe PH without parenchymal lung disease suggest that there could be a specific pulmonary vascular disease. There is no data available on the efficacy of specific pulmonary arterial hypertension treatment in PH-NF1. Therefore, these patients should be evaluated in expert PH centres and referred for lung transplantation at an early stage. As these patients have an increased risk of malignancy, careful assessment of the post-transplant malignancy risk prior to listing for transplantation is necessary. Clinical trials are needed to evaluate promising treatments targeting the RAS-downstream signalling pathways. Pulmonary hypertension is a rare but severe complication of neurofibromatosis type 1. There are no data about the efficacy of specific PAH treatment in this disease and lung transplantation should be discussed at an early stage. http://ow.ly/JMU030lezfY